A CROSS-SECTIONAL STUDY ON ACCEPTANCE AND POST-VACCINATION SYMPTOMS OF COVID-19 VACCINATION IN INDIA - NYAYAKAR, SREEJA; R, SRINIVASAN; L, ARCHANA; S, NITHYANANDAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The fastidious development of the COVID-19 vaccine is a vital achievement for the country and early data suggest that it is both safe and efficacious, however, the acceptance of the COVID-19 vaccine is still a major concern as it depends on the individual decision and sociodemographic characteristics. The main objective of our study is to assess the vaccine acceptance among Indians and study about post-vaccination symptoms to identify potential concerns to be addressed to ensure vaccine safety. Methods: An online cross-sectional study was conducted using Google Forms over a period of 1 week on the general population. Data were collected which included the questions regarding participant demographics, vaccination details, and their health status. Microsoft Excel was used for recording and analyzing the collected data. Results: Out of 1016 respondents, 52% were male and 47.6% were female. Most of the respondents perfectly accept the vaccine, 35.5% are neutral and 5.9% are unacceptable toward vaccination. Post the vaccination of both doses, the occurrence of fever and chills is more common in the case of the first dose, whereas rashes are more common in the second dose, muscle pain and joint pain are common in both doses. Conclusion: This community-based project on acceptance and post-vaccination symptoms of vaccination among Indians reveals that the majority of participants showed a positive acceptance rate toward the vaccination but most of them are worried about the risk of side effects. In regard to post-vaccination symptoms, mild fever and chills are the most common side effect in the case of the first dose of vaccination, whereas muscle/joint pain was seen commonly in both the first and second doses of vaccination.